Parent‐implemented reading interventions within a response to intervention framework. Issue 7 (25th April 2019) - Zhou, Qi; Dufrene, Brad A.; Mercer, Sterett H.; Olmi, D. Joe; Tingstom, Daniel H.
Abstract: This study tested the effects of parent‐implemented reading interventions on four elementary students' reading fluency. Student participants had been receiving a Tier 2 reading intervention, but they were not responding favorably to the Tier 2 intervention. A consultant conducted brief experimental analyses of reading interventions and identified a Tier 3 intervention for each student. Then, the consultant trained the students' mothers to implement the interventions at home. The interventions were tested via a multiple baseline design across students. During the intervention phase, the consultant monitored parents' treatment integrity and assessed students' oral reading fluency for novel, grade‐level progress monitoring passages. Visual analysis indicates that all four students demonstrated increases in oral reading fluency for instructional passages and novel progress monitoring passages after intervention implementation. In addition, single‐case design effect sizes indicate strong effects for instructional passages for all four students, moderate effects for novel progress monitoring passages for two students, and strong effects for novel progress monitoring passages for two students. Finally, parents implemented interventions with moderate to high integrity, and parents rated the interventions as acceptable. Results are discussed in terms of implications for research and practice as they relate to parent‐implemented interventions within a response to intervention framework.